Impact of elementary school-located influenza vaccinations: A stepped wedge trial across a community. Issue 20 (11th May 2018) - Szilagyi, Peter G.; Schaffer, Stanley; Rand, Cynthia M.; Goldstein, Nicolas P.N.; Hightower, A. Dirk; Younge, Mary; Eagan, Ashley; Blumkin, Aaron; Albertin, Christina S.; DiBitetto, Kristine; Concannon, Cathleen; Vincelli, Phyllis; et al.
Abstract: Background: Influenza vaccination rates among children are low and novel strategies are needed to raise coverage. We measured the impact of school-located influenza vaccination (SLIV) on coverage, examined whether SLIV substitutes for practice-based influenza vaccination ("substitution"), and estimated whether a second year of experience with SLIV increases its impact. Methods: We implemented a stepped wedge study design with schools as clusters. In Year 1, we randomly allocated schools to SLIV or control. In Year 2, all schools performed SLIV. We used emails (suburban schools) or backpack fliers (both urban and suburban schools) to notify parents, and offered web-based (suburban) or paper-based vaccination (urban) consent forms. Local health department nurses administered SLIV vaccinations and billed insurers. We analyzed state immunization registry data to measure influenza vaccination rates. Results: 42 schools (38, 078 children) participated over 2 years. Overall vaccination rates were 5 and 7 percentage points higher among SLIV- school children versus control-school children in suburban (aOR 1.36, 95% CI 1.25–1.49 in Years 1–2 SLIV vs. Year 1 control schools) and urban schools (aOR 1.22, 95% CI 1.10–1.36), respectively, adjusting for prior year's vaccination and other covariates. While no substitution occurred among children attending suburban schools, some substitution occurred among children attending urban schools, although overall vaccination rates were still higher in urban schools due to SLIV. Compared to an initial year of SLIV, more children were vaccinated in a second year of SLIV at urban (8.3% vs. 6.8%, aOR 1.24, 95% CI 1.04–1.47) but not suburban schools (3.5% vs. 2.7%, aOR 1.24, 95% CI 0.98–1.57). Conclusions: In this stepped wedge trial, SLIV increased overall influenza vaccination rates in suburban and urban schools. Some substitution for primary care vaccination occurred in urban settings. A second year of SLIV expanded its reach slightly in urban schools.